Corpos (in)dóceis: diversidade sexual e de gênero em uma escola cívico-militar no Maranhão - FERREIRA, Jhonatan Wendell Tavares (2024)
This research, entitled “Docile (In)Bodies: sexual and gender diversity in a civic-military school in Maranhão”, investigates how institutional discourses in a civic-military school (de)regulate the expression of sexual and gender diversity and the government of bodies, with a view to using these discourses in the construction of an educommunication booklet. The specific objectives were to carry out a systematic review of the academic literature identifying and analyzing the main findings and trends on sexual and gender diversity in civic-military schools; to analyze the historical and institutional transformation of military schools in Brazil, from their creation to the implementation of civic-military schools, highlighting the changes in pedagogical, administrative and social aspects; analyze how the discourses present or absent in the formal documents of a civic-military school contribute to the normalization or opening up of dialogues on sexual and gender diversity; understand how the pedagogical/administrative practices of teachers and the management team contribute to the perpetuation and/or deconstruction of traditional gender norms and conventional conceptions of sexuality/gender; and produce an educommunication booklet on sexual and gender diversity. The theoretical basis of the research addresses three main categories, using works by various authors: for the category “Military/militarized colleges/schools”, we adopted the studies of Huntington (2006), Keegan (1995); for the categories: “Body” Foucault (1979; 1987; 1988; 1995), ‘Sexual Diversity’ and ‘Gender Diversity’, we accessed the studies of Butler (2002; 2004; 2018), Lauretis (1994), Oyewumi (2018; 2021), Louro (1997; 2000), Altmann (1998; 2001; 2003). The nature of the research is qualitative, with a methodological approach characterized by collaborative research. The collaborating team was made up of six teachers and two managers. The results reveal a significant gap in the study of issues related to sexual and gender diversity in civic-military schools, highlighting conflicts and dilemmas. In these institutions, there is a constant attempt to control students' bodies, limiting their expression of sexual and gender identity. This rigid control often extends to both student conduct and teaching content, imposing severe surveillance on what can and cannot be discussed in the classroom. This environment of repression tends to stifle the plurality of voices and experiences, creating an educational space that distances itself from the principles of inclusion and respect for diversity. There is therefore an urgent need to open up spaces for dialog that allow these issues to be addressed openly and critically. Promoting debates on sexual and gender diversity is essential for building a more welcoming school environment, where students can exercise their individualities fully and safely. Only through this openness to dialog will it be possible to create a truly inclusive school, capable of preparing its students to live together and respect differences in society. As a result of this research, an educommunication booklet was developed aimed at promoting sexual and gender diversity in military educational environments. The material seeks to raise awareness and guide the school community on the importance of respecting the plurality of identities and sexualities, contributing to the construction of more inclusive and welcoming spaces.